Evaluation of neutrophil-to-lymphocyte ratio as a marker of inflammatory response in spondylodiscitis - Karaarslan, Numan; Yılmaz, İbrahim; Akgün, Feride Sinem; Çalıskan, Tezcan; Doğan, Mustafa; Bilir, Bülent; Ateş, Özkan (My University, 2018)
Aim: Spondylodiscitis, if not diagnosed on time, can cause morbidity or mortality at high rates. This study was carried out with the aim of testing the hypothesis that “neutrophil-to-lymphocyte ratio can be used” especially in cases where it is difficult to diagnose spondylodiscitis. Material and Methods: This study involved 24 patients admitted to the State Hospital of Ministry of Health and Namik Kemal University for spondylodiscitis between January2014 and June2017. After excluding the cases that did not meet the inclusion criteria (n=6), the remaining cases (n=24) were referred to as the study group. A control group was created from healthy volunteers (n=24) who applied for routine physical checkups at the clinic between the same dates and who were similar in terms of age, sex, and body mass index to the study group. Hemogram parameters of the cases in both groups; white blood cell, C-reactive protein, erythrocyte sedimentation rate, and neutrophil-to-lymphocyte ratio were statistically compared. Results: Patients in the spondylodiscitis group, compared to healthy volunteers had statistically significant neutrophil-to-lymphocyte ratio value. Conclusion: Especially in cases where the diagnosis of spondylodiscitis is not assured, the neutrophil-to-lymphocyte ratio parameter, which is less costly than other diagnostic methods and the analysis results of which can be obtained in a shorter time, may be used to support clinical diagnosis.
Keywords: Low Cost Diagnosis Method; Neutrophil-To-Lymphocyte Ratio; Spondylodiscitis